Rule-based systems in balancing the ripple effects of financial services on environmentally impactful sectors - Iulia-Cristina Ciurea (Journal of Research and Innovation for Sustainable Society)
This paper investigates the ripple effects of financial services granted to environmentally impactful sectors such as Oil & Gas, Construction, and Agriculture, focusing on how rule-based systems can influence financial decisions to reduce environmental harm. The objective is to create a framework based on the proposed rule-based system by analyzing existing governmental programs, Environmental, Social, and Governance (ESG) criteria, and green loan criteria that serve as economic mechanisms, guiding financial products toward or away from investments in high-emission industries. The methodology combines theoretical analysis with a proposed rule-based framework that links business rules to credit allocation outcomes. Results from the study suggest that financial institutions, through the implementation of rule-based systems, can effectively balance the need to finance essential sectors without exacerbating environmental damage. The proposed framework allows for more informed lending decisions, mitigating the long-term environmental impacts of financial services on high-emission industries. By aligning economic incentives with sustainability, this paper contributes to the discourse on sustainable finance and environmental risk management.